Invertebrates in the gradient of different age soils under a birdcliff at the Grønfjord Area (Svalbard, Arctic) - N.V. Lebedeva (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2020)
The aim of this study was a preliminary analysis of the distribution of microarthropods (Oribatida, Collembola) and herpetobiontic invertebrates (Aranei, Coleoptera) in soils of different ages under a seabird colony in the vicinity of the Barentsburg settlement (Svalbard). Two transects were established for the sampling: 1) along the slope under the birdcliff in the height gradient from 50 to 100 m a.s.l.; 2) along the slope of the foothill terrace with typical tundra vegetation in the height gradient from 90 to 150 m m a.s.l., where invertebrates were collected by pitfall-traps. Soil samples were taken for the radiocarbon age dating of soils under birdcliff. We collected 389 specimens of invertebrates in both habitats. The formation of bird colony began over 1000 years ago. The highest activity and species diversity were on the slope plot where the radiocarbon age of the soil was about 400 years. The abundance and species structure of invertebrates differ significantly between the two habitats. The invertebrate community is more diverse in the ornithogenic habitat and includes invertebrates of different trophic level, including predators (spiders and rove beetles). Already known for Svalbard 5 species of oribatids (Diapterobates notatus, Ceratoppia sphaerica, Hermannia reticulata, Oribatula tibialis, Tectocepheus velatus), 4 species of spiders (Hilaira glacialis, Erigone arctica palaearctica, E. tirolensis, Mughiphantes sobrius), 7 species of springtails (Hypogastrura viatica, Desoria tshernovi, Folsomia quadrioculata, Isotoma anglicana, Lepidocyrtus lignorum, Sminthurinus сoncolor, Sminthurides malmgreni) and 2 species of rove beetles (Atheta graminicola, Boreophilia subplana) are collected. A new locality has been registered for the rare spider Erigone tirolensis.